Impact of an early educational protocol on the oral language of children born preterm exhibiting phonological fragility: a multicenter randomized clinical trial - Charollais, Aude; Laudenbach, Vincent; Stumpf, Marie-Hélène; Delaporte, Benoît; Datin-Dorriere, Valérie; Debillon, Thierry; De Barace, Claire; Flechelles, Olivier; Farmer, Marie (Frontiers in Psychology, 2024)
We conducted a six-center, prospective, randomized, open-label trial to assess whether an early standardized educational protocol provided from 42 to 48 months of age improved the progression of oral language and phonological development in children born preterm. A total of 552 children with phonological fragility were included in this study. The children were randomized to receive the educational protocol (guided arm, n = 87) or not (non-guided arm, n = 78). In the guided arm, the oral language development used a short “say and do” type educational protocol designed to maintain visual attention and train the developmental phonology/lexicon/morphosyntax structural links. In contrast, a conservative approach was used in the non-guided arm. A total of 70 guided and 73 non-guided children completed the study. After 6 months, the educated children showed a non-significant increase in their phonology score (p = 0.37), while the variations in the scores of the expressive lexicon (secondary endpoints) were significantly improved (p = 0.0008). We conclude that the short, standardized stimulation of the sensorimotor aspects of language in children born very preterm increased the expressive lexicon. This protocol improved the language of the premature children, especially those with minimal motor skills, with more significant improvement in the phonological scores. Clinical trial registration clinicaltrials.gov, identifier NCT01426659